Antioxidant Activity of Methanolic Extract from Date Seeds (Phoenix Dactylifera L.) as A Potential Use of Local Food Waste - Octavia Intan Imanisa; Lilik Wijayanti; Ratih Puspita Febrinasari (Indonesian Journal of Global Health Research, 2025)
Date seeds (Phoenix dactylifera L.) are by-products of the date processing industry that are often discarded, even though they contain potential antioxidant compounds. This study aimed to evaluate the antioxidant activity of methanolic extract from date seeds as a sustainable approach to valorizing food waste. The research was conducted at the Laboratory of the Center for Food and Nutrition Studies, Universitas Gadjah Mada. Date seeds were obtained from small-scale food industries in Klaten, Central Java, then cleaned, dried, macerated, and sieved through mesh 80. A total of 50 grams of powdered seeds were extracted using the Soxhlet method with methanol for 6 hours. The antioxidant activity was measured using the DPPH method by reading the absorbance at 515 nm. The results showed DPPH radical inhibition percentages of 58.87% and 48.75% in two replications, with an average of 53.81%. The data were analyzed descriptively based on the percentage of radical scavenging activity. These findings suggest that date seeds possess considerable antioxidant activity and can be utilized as a natural antioxidant source, while also supporting the upcycling of local food waste into functional food ingredients.